Organizational-Pedagogical Conditions of Professional Self-Perfection of the Head of General Educational Institution - Levchenko, Liudmyla (Pedagogical Discourse, 2015)
In the article on the basis of analysis of scientific literature and experimental research, basic organizational and pedagogical conditions of professional self-perfection of the head of general educational institution have been determined. It is revealed that managerial competence of the headmaster of school assumes knowledge of the theory of management of school as an open complex socio-pedagogical system of laws, regularities, scientific approaches and principles of school management, ways of their implementation, content management of school. It is found out that the head of modern general educational institution should have the skills of new thinking that is associated with the penetration of management into the managerial activity of the heads of educational institutions. In the process of the analysis of practical implementation of organizational-pedagogical bases of administrative activity of the head of general educational institution it is proposed to improve the ways of mastering of such activity. The key educational direction of self-education organization of the head of general educational institution for the constant professional growth have been determined. The main objectives of the teaching unions, in particular ensuring the continuous professional development of the heads of the system of general secondary education, implementation of scientific support of innovations in the managerial area, promotion of the development of the system of general secondary education.